Kebijakan Pendidikan dan Media Sosial Sebagai Faktor Pembentukan Preferensi Politik Pemilih Pemula di Kota Makassar - Yunus, Ariana; Tamma, Sukri; Ekawaty, Dian (Departemen Ilmu Administrasi FISIP UNHAS, 2021)
This paper aims to show how the formation of political preferences of first-time voters occurs. As a factor that influences political behavior, the understanding of political preferences becomes important thinking of a person or community, including the first-time voters. As one of the important segments in political dynamics, first-time voter existence is always an interesting aspect to be examined, including their existence as people who are about to exercise their voting rights for the first time. So far, the first-time voters have tended to be seen as a segment that seems simply to understand their political behavior tendencies due to assumed it is often reflecting the political attitudes of their parents or family. However, since the emergence of social media, there has been a tendency of shifted related to their forming political preferences. Based on research conducted in the City of Makassar towards students in several high schools as first-time voters, this paper aims to show how the actual role of schools, parents, and social media roles in shaping their political preferences that shaping the tendency of their political behavior.